RISKS OF A COMMERCIAL BANK AND ITS MANAGEMENT METHODS - Egamova Mahfurat Esanovna (European Science Publishing, 2025)
Banking risk management is related to how a credit institution determines the risks it faces. Consistent optimal management and further classification of banking risks is very important for risk management, as ambiguity can lead to confusing reporting and management of banking risks. This article examines and studies different sources of the concept of "banking risk" and their classification, as well as methods of banking risk management. When considering banking risks, we have developed a specific classification based on various criteria.
Keywords: Risk, management, classification, banking, systematization, attribute, group.